Growing up in a recession: beliefs and the macroeconomy - Paola Giuliano; Antonio Spilimbergo (Institute for the Study of Labor (IZA), 2009)
Do generations growing up during recessions have different socio-economic beliefs than generations growing up in good times? We study the relationship between recessions and beliefs by matching macroeconomic shocks during early adulthood with self-reported answers from the General Social Survey. Using time and regional variations in macroeconomic conditions to identify the effect of recessions on beliefs, we show that individuals growing up during recessions tend to believe that success in life depends more on luck than on effort, support more government redistribution, but are less confident in public institutions. Moreover, we find that recessions have a long-lasting effect on individuals' beliefs.
urn:nbn:de:101:1-2009092850
Keywords: P16; E60; Z13; 330; Beliefs formation; macroeconomic shocks; Wirtschaftslage; Schock; Wirtschaftspolitik; Jugendliche; Weltanschauung; Persönlichkeitspsychologie; USA